Relative active tectonics evaluation using geomorphic and drainage indices, in Dadra and Nagar Haveli, western India - Naveen Kumar; Rakesh K. Dumka; Kapil Mohan; Sumer Chopra (Geodesy and Geodynamics, 2022)
The present study area, Dadra and Nagar Haveli, contains several lineaments and traces of active faults. The various aspect of the geomorphic analysis, i.e., stream length (SL) gradient, hypsometric integral (HI), basin shape (BS), valley floor (VF), have been applied to evaluate the relative index of active tectonics (RIAT) of the Damanganga watershed. The high and low zones of tectonic activity have been identified based on the geomorphic analysis of the watershed. After evaluation of all indices, three classes, class II- high (1.3 ≤ RIAT < 1.5), class III- moderate (1.5 ≤ RIAT < 1.8), and class IV- low (1.8 ≤ RIAT), have been obtained to outline the degree/gradation of comparative tectonic activities in the study area. The appraised outcome of the RIAT dispersal is also well reinforced by the geomorphic evidence in the field. The collective outcomes of geomorphic evidence, such as stream deflection and analysis of lineament, deflection of streams, and geomorphic indices, conceal that the Damanganga watershed is affected by tectonic activity.